2008
DOI: 10.1124/jpet.108.143123
|View full text |Cite
|
Sign up to set email alerts
|

A Positive Modulator of KCa2 and KCa3 Channels, 4,5-Dichloro-1,3-diethyl-1,3-dihydro-benzoimidazol-2-one (NS4591), Inhibits Bladder Afferent Firing in Vitro and Bladder Overactivity in Vivo

Abstract: Calcium-activated potassium channels are attractive targets for the development of therapeutics for overactive bladder. In the current study, we addressed the role of calcium-activated potassium channels of small (SK; K Ca 2) and intermediate (IK; K Ca 3) conductance in bladder function pharmacologically. We identified and characterized a novel positive modulator of SK/IK channels, 4,5-dichloro-1,3-diethyl-1,3-dihydro-benzoimidazol-2-one (NS4591). In whole-cell patch-clamp experiments, NS4591 doubled IK-mediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
47
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(52 citation statements)
references
References 27 publications
4
47
1
Order By: Relevance
“…It has previously been reported that Tl 1 influx can be monitored in FLIPR assays to detect activation of K 1 channels such as K v 7.2 and K Ca 2.3 (Weaver et al, 2004). In addition, our earlier studies demonstrated the capacity to detect activators of another Ca 21 -activated K 1 channel (hK Ca 3.1) in a similar assay (Hougaard et al, 2009;Jørgensen et al, 2013). The BK Tl 1 influx assay described in the current study appears to be highly suitable for detecting new smallmolecule BK activators.…”
Section: Discussionmentioning
confidence: 89%
“…It has previously been reported that Tl 1 influx can be monitored in FLIPR assays to detect activation of K 1 channels such as K v 7.2 and K Ca 2.3 (Weaver et al, 2004). In addition, our earlier studies demonstrated the capacity to detect activators of another Ca 21 -activated K 1 channel (hK Ca 3.1) in a similar assay (Hougaard et al, 2009;Jørgensen et al, 2013). The BK Tl 1 influx assay described in the current study appears to be highly suitable for detecting new smallmolecule BK activators.…”
Section: Discussionmentioning
confidence: 89%
“…6,7-Dichloro-1H-indole-2,3-dione-3-oxime (NS309), a potent SK/IK channel activator (Strøbaek et al, 2004), increases bladder capacity and decreases voiding frequency in rats (Pandita et al, 2006), but its extremely short half-life precludes in vivo application. 4,5-Dichloro-1,3-diethyl-1,3-dihydro-benzoimidazol-2-one (NS4591), another SK/IK channel activator, inhibits DSM carbachol-induced contractions in vitro and bladder overactivity in vivo (Hougaard et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Bladder ring preparations were obtained from six female Sprague-Dawley rats ( ∼ 200 g) [7]. Bladder samples were obtained from nine female pigs (6 months, 75-95 kg).…”
Section: Methodsmentioning
confidence: 99%
“…4,5-dichloro-1,3-diethyl-1,3-dihydrobenzoimidazol-2-one (NS4591) is a new positive modulator of SK/IK channels that has been shown to inhibit the number of action potentials in bladder primary afferent neurons generated by suprathreshold depolarizing pulses. NS4591 also reduced carbachol-induced twitches in rat bladder rings in an apamin (a specific inhibitor of SK channels) -sensitive manner and, in vivo , NS4591 inhibited detrusor overactivity induced by capsaicin and acetic acid in rats and cats, respectively [7].…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation